Evaluation of acute and subacute toxicity and sedative effect of Feretia apodanthera Delile (Rubiaceae) leaves - Gniènèfèrètien Nounaféri Awa Silué; Sylvain Ilboudo; Lenoir Thierry Ayoman Djadji; Geoffroy Ouedraogo; Mohamed Bonewendé Belemlilga; Gisèle Kouakou-Siransy; Rasmané Semdé (Elsevier, 2024)
Introduction: Medicinal plants have experienced a resurgence in usage over recent decades. Indeed, they constitute a therapeutic resource for a considerable proportion of the world's population. Nevertheless, evaluating the safety of these plants remains a challenge in ensuring their secure utilisation. Aim: The aim of this study was to assess the safety, tolerability and sedative effect of Feretia apodanthera Methods: A lyophilised aqueous infusion of Feretia apodanthera was prepared from dried leaf powder. The Organisation for Economic Co-operation and Development (OECD) guidelines 423 and 407 were employed. The initial assessment of acute toxicity was conducted by administering a single dose of 2,000 mg kg-1 of lyophilisate to female rats, after which the animals were observed for a period of 14 days. In a subsequent series of experiments, the subacute toxicity of the lyophilisate was evaluated through daily administrations of doses of 250 mg kg-1, 500 mg kg-1 and 1,000 mg kg-1 to both male and female rats over a period of 28 days. Furthermore, the potential sedative effect of the lyophilisate was investigated in mice. Results: In both single administration and repeated administration over 28 days in rats, the lyophilisate of the aqueous infusion of Feretia apodanthera did not induce mortality or significant changes in weight progression, water and food consumption, relative organ weights, or biochemical and haematological parameters, compared to the controls. However, it potentiated diazepam-induced sleep in mice. This sedative effect appears to involve an interaction with GABAA receptors. Conclusion: Although the sedative effect should be taken into account during use, the aqueous leaf infusion of Feretia apodanthera appears to be relatively well tolerated in both single and repeated administrations.